PORTFOLIO MODELING AND SELECTION OF PROJECTS FOR IMPLEMENTATION OF THE STRATEGY FOR INNOVATION GIVEN NETWORK ARCHITECTURE MANAGEMENT AT THE ENTERPRISES OF THE INDUSTRIAL COMPLEX - Elena Yu. Rebiy (Вестник Северо-Кавказского федерального университета, 2022)
Innovative enterprises operate in the conditions of uncertainty - it is necessary to consider when choosing a system of criteria for evaluation and selection of innovative projects that require adjustments in the decision-making process. Mandatory requirements become finding attractive innovation projects, and their estimation in conditions of incomplete information.